2022
DOI: 10.1111/jcmm.17453
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stemness mediated by BMI1 and MCL1 for non‐small cell lung cancer treatment

Abstract: Lung cancer is the leading cause of cancer‐associated death, with a global 5‐year survival rate <20%. Early metastasis and recurrence remain major challenges for lung cancer treatment. The stemness property of cancer cells has been suggested to play a key role in cancer plasticity, metastasis and drug‐resistance, and is a potential target for drug development. In this study, we found that in non‐small cell lung cancer (NSCLC), BMI1 and MCL1 play crucial roles of cancer stemness including invasion, chemo‐resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Existing studies have also conducted preliminary exploration into the role of BMI1 in NSCLC progression and chemotherapy drug resistance [40,41]. In this study, we observed a signi cant negative correlation between the expression of SOX4 and BMI1 in NSCLC tissues, and patients with high expression of both had worse prognoses.…”
Section: Discussionmentioning
confidence: 48%
“…Existing studies have also conducted preliminary exploration into the role of BMI1 in NSCLC progression and chemotherapy drug resistance [40,41]. In this study, we observed a signi cant negative correlation between the expression of SOX4 and BMI1 in NSCLC tissues, and patients with high expression of both had worse prognoses.…”
Section: Discussionmentioning
confidence: 48%
“…Zhou et al found targeting c-KIT can inhibit the growth and invasion of gefitinib-resistant NSCLC cells by reducing cancer stemness, EMT, and acquired drug resistance [ 67 ]. In lung cancer, MCL1 has been suggested to play a key role in cancer stem cells, including invasion, chemotherapy resistance, and tumorigenesis [ 68 ]. In NSCLC patients with EGFR mutations, the BIM deletion polymorphism results in an inherent resistance or reduced sensitivity to EGFR TKIs [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a heterodimers RING E3, BMI1 can induce H2A ubiquitylation at Lys 119. BMI1 can induce ubiquitination and degradation of NLR family CARD domain containing 5 (NLRC5), given that BMI1 can facilitate immune escape in NSCLC [ 58 , 62 ]. Thyroid Hormone Receptor Interacting Protein 12 (TRIP12), a HECT E3, also known as Ubiquitin Ligase for ARF (ULF) [ 63 ], ubiquitinates and degrades nuclear factor of activated T cells 1 (NFATc1), thereby downregulating PD-1 expression, resulting in increasing cancer infiltrating CD8 + T cells and inhibition in LLC growth in mice [ 64 ].…”
Section: Advanced Researches On the Functions Of E3 Ligases In Lung C...mentioning
confidence: 99%